Rural Finance Policies 10 - Assessing the relative poverty level in clients of microfinance institutions: an operational tool - Zeller, Manfred; Sharma, Manohar (2000)
Many microfinance institutions (MFIs) receive public support. In return for this support, governments and donors demand MFIs not only become financially sustainable but also reach the poor, or even the poorest of the poor. Effective evaluation of the achievement of these objectives requires appraising both the MFI’s financial sustainability and the relative poverty of its clients. In recent years, several tools have emerged to assist donors in their assessment of the financial sustainability of MFIs. For example, the Consultative Group to Assist the Poorest (CGAP), which seeks to promote sustainable microfinance institutions for the poor, disseminates a number of tools that allow assessing the financial sustainability and other aspects of institutional performance of MFIs. Currently, no operational tool exists for measuring how well a MFI reaches the poor through its services. In order to gain more transparency on the depth of poverty outreach, CGAP supported research at IFPRI during 1999 and 2000 to design and test a simple, low-cost operational tool to measure the poverty level of MFI clients relative to nonclients. This policy brief summarizes the main features of the tool, how it can be applied, and what type of results can be obtained.